2021
DOI: 10.4049/jimmunol.2000502
|View full text |Cite
|
Sign up to set email alerts
|

The Skin–Liver Axis Modulates the Psoriasiform Phenotype and Involves Leucine-Rich α-2 Glycoprotein

Abstract: Leucine-rich α-2 glycoprotein (LRG), one of the acute phase proteins mainly produced by the liver, similar to C-reactive protein, has been recognized as an inflammatory biomarker for rheumatoid arthritis and inflammatory bowel diseases. We recently demonstrated that LRG was also increased in the sera of psoriasis patients and correlated well with disease activity with a sensitivity and specificity much higher than C-reactive protein; however, whether LRG mechanistically contributed to the pathogenesis of psori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Among those, autoimmune diseases are particularly disabling conditions representing a major hurdle both in terms of diagnosis and treatment. In particular, serum LRG1 has been identified as a useful biomarker for monitoring disease activity in patients with adult-onset Still's disease [ 138 ], psoriasis [ 65 , 139 , 140 ] lupus nephritis [ 17 ], rheumatoid arthritis [ 141 144 ] and vasculitis [ 145 149 ]. However, the role of LRG1 in these conditions remains largely unclear.…”
Section: Reviewmentioning
confidence: 99%
“…Among those, autoimmune diseases are particularly disabling conditions representing a major hurdle both in terms of diagnosis and treatment. In particular, serum LRG1 has been identified as a useful biomarker for monitoring disease activity in patients with adult-onset Still's disease [ 138 ], psoriasis [ 65 , 139 , 140 ] lupus nephritis [ 17 ], rheumatoid arthritis [ 141 144 ] and vasculitis [ 145 149 ]. However, the role of LRG1 in these conditions remains largely unclear.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have shown that persistently high levels of LRG1 can maintain an inflammatory response and promote disease progression through a wide range of biological functions [22]. At present, it has been reported that LRG1 might be a useful biomarker to detect the occurrence of psoriasis in adults [23][24][25]. The development of new biomarkers has an urgent clinical need for early diagnosis and management of certain inflammatory diseases, and LRG1 is regulated by various pro-inflammatory cytokines, making it a highly promising candidate drug target for development [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adiponectin, other factors have been suggested to be involved in the liver–skin axis. Leucine-rich α-2 glycoprotein (LRG) modulates the liver–skin axis and is involved in the pathogenesis of psoriasiform inflammation ( 44 ). LRG deficiency resulted in mild psoriatic skin changes associated with decreased inflammatory cytokine expression in a murine model of psoriasis.…”
Section: Discussionmentioning
confidence: 99%